AN EFFICACY OF VIRECHANA KARMA IN THE MANAGEMENT OF VICHARCHIKA (AYUSHDHARA, 2017)
Samshodhana is the bio-purification of the body which is performed in the Bahudosha Avastha i.e. Kushtha, Prameha etc. Moreover, Panchakarma therapy is one of the important parts of Chikitsa which comes under the Shamshodhana. Among five Karmas, Virechana is the best line of treatment for Pittaja and Rakta Pradoshaja Vikara. Vicharchika i.e., Kshudrakushtha comes under the Rakta Pradoshaja Vikara with Pitta-Kapha dominancy. Vicharchika presents with symptoms of Sakandu, Pidaka, Shyavata and Bahusrava and its similar clinical presentation in modern dermatology can be traced as Eczema. The modern science has greatly advanced particularly in dermatology; few drugs are available only for symptomatic relief. For symptomatic treatments steroids are used, but they produce serious side effects like nephrotoxicity, osteoporosis, skin cancer etc. Eczema also has tendency of recurrence which pose problems to the physician. Therefore, the whole world is looking towards Ayurveda for this problem. Considering all the above facts and figures in mind, the present study has been planned to assess the efficacy of Virechana Karma in the management of Vicharchika. For this purpose patients were randomly selected from O.P.D. & I.P.D. of SMBT Ayurved College & Hospital, Dhamangoan and giving them Virechana therapy. Virechana therapy shows that 64.70%, 56.52%, 46.42% and 70.96% relief were observed in cardinal symptoms Kandu, Pidaka, Shyavavarnyata and Bahausrava respectively. While in associate symptoms Shotha, Daha and Vedana 61.53%, 55.55% and 57.14% relief were found respectively. Moreover, Virechana provided marked improvement, moderate and mild improvement to 20%, 50% and 30% patients respectively. Hence we can say that Virechana Karma gives better relief in all symptoms of Vicharchika. Vicharchika (Eczema) has tendency to recurrence. So, it should be advisable to repeat the Virechana Karma as per the need and at proper time to provide better result to patients.